Can contract farming improve farmers’ technical efficiency and income? Evidence from beef cattle farmers in China - Liang, Yuan; Bi, Wentai; Zhang, Yuejie (Frontiers in Sustainable Food Systems, 2023)
Introduction Contract farming is seen as a tool to create new market opportunities that can address market imperfections in many developing countries and thus increase smallholder income. Methods This study examines the impact of contract farming on farm household income using survey data from 610 rural households in China. The propensity score matching method addresses the sample selection bias of participation in contract farming. Results Contract farming can significantly increase farmers’ income, and both marketing contracts and production-management contracts can substantially increase farmers’ income levels, with production-management contracts having a greater degree of impact. Additional analysis reveals that breeding years, farm size, and training time can significantly affect how contract farming enhances farmers’ income. At the same time, contract farming can also considerably improve farmers’ technical efficiency in agricultural production. Participation in contract farming enhances the tendency to centralize the technical efficiency of agricultural production. Further analysis shows that the technical efficiency of agricultural production partially mediates the effects of contract farming on farm household income. Discussion Contract farming can be an effective institutional arrangement for improving the technical efficiency of farm household production and revenue. We also point out that farmers should strengthen their comprehensive ability levels and actively participate in training to acquire new knowledge and improve their cognitive ability. Simultaneously, according to the characteristics of farmers’ resource endowments, small farmers are encouraged to cooperate with companies in depth and develop contractual contracts in a targeted manner. Promote win-win cooperation and benefit-sharing among various business entities to promote the sustainable and high-quality development of China’s beef cattle industry.